International BEAT-PCD consensus statement for infection prevention and control for primary ciliary dyskinesia in collaboration with ERN-LUNG PCD Core Network and patient representatives. Issue 3 (2nd August 2021) - Marthin, June K.; Lucas, Jane S.; Boon, Mieke; Casaulta, Carmen; Crowley, Suzanne; Destouches, Damien M.S.; Eber, Ernst; Escribano, Amparo; Haarman, Eric; Hogg, Claire; Maitre, Bernard; Marsh, Gemma; et al.
Introduction: In primary ciliary dyskinesia (PCD) impaired mucociliary clearance leads to recurrent airway infections and progressive lung destruction, and concern over chronic airway infection and patient-to-patient transmission is considerable. So far, there has been no defined consensus on how to control infection across centres caring for patients with PCD. Within the BEAT-PCD network, COST Action and ERS CRC together with the ERN-Lung PCD core a first initiative has now been taken towards creating such a consensus statement. Methods: A multidisciplinary international PCD expert panel was set up to create a consensus statement for infection prevention and control (IP&C) for PCD, covering diagnostic microbiology, infection prevention for specific pathogens considered indicated for treatment and segregation aspects. Using a modified Delphi process, consensus to a statement demanded at least 80% agreement within the PCD expert panel group. Patient organisation representatives were involved throughout the process. Results: We present a consensus statement on 20 IP&C statements for PCD including suggested actions for microbiological identification, indications for treatment of Pseudomonas aeruginosa, Burkholderia cepacia and nontuberculous mycobacteria and suggested segregation aspects aimed to minimise patient-to-patient transmission of infections whether in-hospital, in PCD clinics or wards, or out of hospital at meetings between people with PCD. The statement also includes segregation aspects adapted to the current coronavirus disease 2019 (COVID-19) pandemic. Conclusion: The first ever international consensus statement on IP&C intended specifically for PCD is presented and is targeted at clinicians managing paediatric and adult patients with PCD, microbiologists, patient organisations and not least the patients and their families. For the first time ever, an international consensus statement for infection prevention and control in PCD is presented. A total of 20 statements were developed in a collaboration of BEAT-PCD, COST Action, ERS CRC and ERN-LUNG PCD Core Network. https://bit.ly/3yuahKt